1998
DOI: 10.1080/01443619866778
|View full text |Cite
|
Sign up to set email alerts
|

Low values on 50 gram glucose challenge test or oral 100 gram glucose tolerance test are associated with good perinatal outcome

Abstract: We set out to reevaluate the hypothesis that high normal (negative) results of 50 g oral glucose challenge test or high normal glucose level on 100 g oral glucose tolerance test are associated with complications of pregnancy and delivery. This was a prospective study involving 735 nondiabetic women. The first group (n=352) was made up of pregnant women with normal 50 g oral glucose challenge test without previous history of diabetes mellitus or gestational diabetes. The second group (n=383) was made up of preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Women whose BG level ≥7.8 mmol/L (140 mg/dL) at the GCT are more likely to have a larger baby at birth. 35 We excluded those women from this study to avoid the potential bias on the observed risk association of SGA with low BG. Maternal low BG levels suggest a low energy supply capacity that may cause problems for normal fetal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Women whose BG level ≥7.8 mmol/L (140 mg/dL) at the GCT are more likely to have a larger baby at birth. 35 We excluded those women from this study to avoid the potential bias on the observed risk association of SGA with low BG. Maternal low BG levels suggest a low energy supply capacity that may cause problems for normal fetal growth.…”
Section: Discussionmentioning
confidence: 99%